PESAN PENDERITA KANKER DALAM FILM CLOUDS: PRESPEKTIF SEMIOTIKA PEIRCE - Sendi Rahman Hakim; Dylan Abyaksa; Eva Dwi Kurniawan (CALACCITRA: JURNAL FILM DAN TELEVISI, 2023)
The film Clouds tells the story of the struggle of a 17-year-old teenager against bone cancer or Osteosarcoma, which he has suffered since he was 14 years old. Many messages are given by this film. These messages need to be disclosed and explained in more depth so that they can provide wider benefits, especially to people with cancer in particular, and society in general. The purpose of this study is to explore the messages conveyed by cancer patients shown in film scenes. The formulation of the problem in this study is how are the messages that can be extracted related to the story of cancer patients contained in the film Clouds? This research method uses Charles Sanders Peirce's semiotic approach. The technique used is by analyzing several scenes in the film that are related to the formulation of the problem. The findings obtained show that the message of a cancer patient in the film Cloud includes not expecting compassion; showing a happy smile; value time; keep working; and never give up.